2006
DOI: 10.2166/wqrj.2006.033
|View full text |Cite
|
Sign up to set email alerts
|

Using Pilot-Scale Investigations to Estimate the Remaining Geosmin and MIB Removal Capacity of Full-Scale GAC-Capped Drinking Water Filters

Abstract: Pilot tests were conducted to investigate the removal of geosmin and 2-methylisoborneol (MIB) by new and semi-exhausted granular activated carbon (GAC) extracted from full-scale filters located in the City of Toronto's drinking water treatment facilities. Four pilot filters containing core-sampled GAC and new sand were fed with settled water from a full-scale plant and operated under conditions similar to those employed at full-scale. None of the pilot filters appeared to be capable of reducing geosmin and MIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…Canada. Furthermore, Ndiongue et al (2006) demonstrated that an increase of GAC depth to 95 cm, and an increase of EBCT from 2.8 min to maximum 7.5 min, significantly increased geosmin removal efficiency of used GAC by around 35% which further supports the results of this study. Fig.…”
Section: Bench Scale Studysupporting
confidence: 88%
See 1 more Smart Citation
“…Canada. Furthermore, Ndiongue et al (2006) demonstrated that an increase of GAC depth to 95 cm, and an increase of EBCT from 2.8 min to maximum 7.5 min, significantly increased geosmin removal efficiency of used GAC by around 35% which further supports the results of this study. Fig.…”
Section: Bench Scale Studysupporting
confidence: 88%
“…8a). The degree of removal was comparable with that reported by Ndiongue et al (2006), 61e75% and 24e47% geosmin removal using 25 cm of virgin and used (about 3 years), bituminous GAC at 2.8 min EBCT, respectively, at three full-scale WTPs located in southern Ontario, Table 1. Canada.…”
Section: Bench Scale Studysupporting
confidence: 87%
“…6) and without (data not shown) H 2 O 2 quenching. Ndiongue et al 45 demonstrated that an increase in GAC depth or EBCT would significantly improve the removal of geosmin and MIB from water. Furthermore, other studies have also observed better (minimum 13%) geosmin removal compared to MIB removal by GAC.…”
Section: Resultsmentioning
confidence: 99%